Experiences of living with binge eating disorder and facilitators of recovery processes: a qualitative study - Marit Fjerdingren Bremer; Lisa Garnweidner-Holme; Linda Nesse; Marianne Molin (Journal of Eating Disorders, 2023)
Abstract Background Binge eating disorder (BED) is the most prevalent eating disorder worldwide. BED is often associated with low quality of life and mental health problems. Given the complexity of the disorder, recovery may be challenging. Since BED was only recently specified as a diagnostic category by the World Health Organization (2021), little is known about how patients experience living with BED in everyday life. This study aimed to explore how patients experience living with BED and to investigate factors perceived as facilitating recovery. Method Individual interviews were conducted with six patients in a rehabilitation programme for recovery from BED. Interviews were conducted digitally and verbally transcribed between December 2020 and January 2021. The analysis was based on Malterud’s systematic text condensation. Results Being diagnosed with BED could be experienced as a relief. The participants perceived living with BED as a challenging addiction. They struggled with a low self-image and experienced a lack of understanding from others, resulting in shame. Self-compassion and social support from friends and family and through participation in a rehabilitation programme were important facilitators of recovery. Conclusion Participants perceived living with BED as a challenging addiction. They struggled with low self-esteem and experienced a lack of understanding from others, resulting in shame. Being diagnosed with BED was perceived as a relief. They appreciated that issues related to mental health were addressed during rehabilitation to better understand the complexity of BED. Knowledge about BED, as well as the difficulties of living with BED among family members and friends might help patients with BED feel less ashamed of their disorder and could thus contribute to increased self-compassion.